PENGARUH DIVERSIFIKASI PENDAPATAN TERHADAP KINERJA BANK; STUDI EMPIRIS PADA BANK KOMERSIAL DI ASIA - Devi Febrianti; Miuzuddin (JURNAL FAIRNESS, 2023)
The purpose of this study is to examine the effect of income diversification on bank performance in the Asian countries. This study uses bank-level data from BankFocus for 173 banks in 8 countries in the Asian for the period 2011-2019. Meanwhile, the data at the country level uses data obtained from the World Bank. The results show that income diversification can reduce bank profitability and efficiency. The results suggest that, although diversification theoretically offers benefits to banks, it has consequences. To improve supervisory performance, risk-taking behavior and understanding of the bank's core business are important concerns in implementing diversification.